Penyakit Ginjal Kronik Stadium V Akibat nefrolitiasis - Helen Widiani (Intisari Sains Medis, 2020)
Background: Chronic kidney disease (CKD) is a kidney disorder characterized by abnormality in kidney structure and its function for more than three months, or decrease of glomerular filtration rate less than 60 ml/minute/1.73m2. The cause of CKD including hypertension, diabetes mellitus, obstruction in urinary tract and infection.Case description: male 34 years old hospitalized with chief complaint of nausea and vomiting since 10 days before admission. The patient also complained of pain in the right flank since one year. The urination tend to decrease since one week before admission. Phsyical examination found the patient in moderate illness, anemic in conjungtiva, pain in costovertebral angle with edema in inferior extremities. Radiology examination revealed nefrolitiasis in right region, grade II hydronephrosis caused by stone in distal ureter and cystitis. Abdominal CT-Scan revealed mild hydronephrosis caused by stone in pyelum, with nephrolithiasis in right part. Conclusion: Chronic kidney disease is an injury in kidney which occur for more than three months, according to pathological abnormality or kidney injury marker like. Its management renal replacement therapy, diet for CKD patients, and controlling the hypertension (its comorbid condition).Latar belakang: Penyakit Ginjal Kronik (PGK) merupakan suatu gangguan pada ginjal yang ditandai dengan abnormalitas struktur dan fungsi ginjal yang berlangsung lebih dari tiga bulan, atau penurunan laju filtrasi glomerulus kurang dari 60 ml/menit/1,73 m2.Deskripsi kasus: Seorang pasien laki-laki usia 34 tahun dirawat dengan keluhan utama mual dan muntah dialami sejak 10 hari sebelum masuk rumah sakit. Pasien juga mengeluhkan nyeri pinggang kanan yang dialami sejak 1 tahun terakhir. Buang air kecil sedikit-sedikit dialami sejak 1 minggu sebelum masuk rumah sakit. Dari pemeriksaan fisik pasien tampak sakit sedang, konjungtiva anemis, nyeri ketok CVA, dan ditemukan edema pada ekstremitas inferior. Pada pemeriksaan radiologi didapatkan nefrolitiasis dextra, hidronefrosis grade II akibat batu distal ureter, sistitis. Pemeriksaan CT-Scan abdomen didapatkan kesan hidronefrosis ringan akibat batu pyelum, nefrolitiasis kanan. Kesimpulan: Penyakit ginjal kronik (PGK) merupakan kerusakan ginjal yang telah terjadi dalam kurun waktu lebih dari tiga bulan, yang ditandai dari kelainan patologis atau petanda kerusakan ginjal. Tatalaksana yang diberikan pada pasien meliputi terapi berupa terapi pengganti ginjal, diet khusus pada pasien dengan PGK, serta pengaturan tekanan darah pasien (penanganan pada kondisi komorbid).